CULTURE AS A CREATIVE BASE OF EDUCATION - C. Z. Goncharov (Образование и наука)
The paper denotes the vital need for the human-centered pro jects of education updates and develops the idea of the culture adequacy raised by Y. V. Larin in «Education in search of the adequacy principle». The author regards culture as a creative basis for upbringing the young generation, and provides the detailed analysis of its semantic content; in his opinion, culture contains neither value neutral nor destructive connotations. The world of culture incorporates the model samples of human subjectivity, based on the main criterion of perfection. By revealing the model samples of cultural heritage to students, a teacher develops their general cultural competences and the related individual, professional and civic qualities. Consequently, the author argues that socio-economic and political problems, including the renovation of social institutions and industrial spheres, can be solved by cultivating and developing the universality and integrity of productive and creative human forces. Additionally, the paper proves the impossibility of separate development of the general cultural and professional competences in educational process.